A meta-analysis of randomised controlled trials investigating the impact of colchicine on major adverse cardiovascular events in acute coronary syndrome. (14th October 2021) - Blake, N; Alonso, A; Rai, H; Colleran, R; Giacoppo, D; Byrne, R A; ,
Abstract: Background/Introduction: Colchicine has been shown to reduce inflammation and has a potential to stabilise atherosclerotic plaques. Prior meta-analyses on the topic suggest its role in reducing components of major adverse cardiovascular events (MACE). Purpose: The aim of the present meta-analysis was to delineate the effect of colchicine on post-PCI (percutaneous intervention) MACE among acute coronary syndrome (ACS) patients. Methods: We included randomised controlled trials (RCTs) comparing colchicine to placebo in ACS patients undergoing PCI. To identify potentially relevant trials a PUBMED search was undertaken using the MESH terms "colchicine" and "cardiovascular system". Eligible RCTs published up to November 2020 were included. Our search strategy also included presentations from the proceedings of international meetings. The primary endpoint was MACE. However, definitions of MACE varied between included studies. Study level odds ratios (ORs) and 95% confidence intervals (CI) of MACE were pooled using the Mantel-Haenszel method and random effects model. Forest plots were generated using Review Manager (RevMan) 5.4 software. Results: Our initial search identified 1, 049 articles for potential inclusion. Of them, 4 RCTs were found to be eligible: COPS, COLCHICINE-PCI, COLCOT time-to-Initiation (TTI) 0–3 days and PODCAST-PCI. A pool of 2, 709 patients were randomly allocated to treatment with either colchicine (n=1, 367) or placebo (n=1, 342). Patients received colchicine either prior to angiography or within 3 days post-procedure. Follow up duration ranged from 30 days to 3 years during which MACE were recorded. Mean age of the whole analysed cohort was 60.3±10.5 years. 73% were male. 51% had history of hypertension, 26% had diabetes mellitus, 38% were current smokers. There were 89 events in the colchicine group as opposed to 133 events in the placebo group. The risk of post-PCI MACE was lower in patients treated with colchicine as compared with placebo (OR 0.63, 95% CI 0.48–0.84, p=0.001) (see figure 1). Heterogeneity was not detectable (I 2 =0). Conclusions: Our results indicate lower risk of MACE in patients treated with colchicine. This indicates a potential use of colchicine in patients undergoing PCI in an ACS setting. Further investigations in larger cohorts are warranted to test this effect. FUNDunding Acknowledgement: Type of funding sources: None.